Visual Simulation of Chocking Training to Education Mother with Babies in Pandemic Covid-19 - Rimawati Rimawati; Heru Suwardianto (Universitas STRADA Indonesia, 2022)
Background: Chocking is a dangerous one out of the hospital. Many mothers with babies do not give do not understand prevention efforts when the baby is choking. The research objective was to determine the effectiveness of visual stimulation of choking training to educate mothersMethods:The research design was pre-experimental. The population was all mothers in Kediri City, East Java Province- Indonesia. The independent variables were video simulation of choking training. The dependent variable was knowledge and Skills. Results: The knowledge variable obtained a Z value of -4.8 with a P-value = <0.05 and the choking treatment variable with a Z value of -4.6 with a P-value = <0.05 which means there is a significant effect of video simulation chocking training can improve knowledge and improvement of choking management skills in respondents. Conclusions: Prevention is more important in reducing the morbidity of cases related the incidence of choking in infants.